Infinite Correspondence - Pyenson, Lucas (Tufts Archival Research Center, 2005)
A brief history of French and Arab cookbooks, as well as French influence on North African cuisine, and North African influence on French cuisine. Food is looked at as a visual discipline. This is followed by an original 12-course dinner exploring socio-cultural relationships between the Middle East, North Africa, France, and the Southern Mediterranean. The actual dinner took place on April 22nd, 2012, between 6:30 and 9:30pm.